2014
DOI: 10.5350/semb.20140219060126
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and threshold of the erythrocyte suspension transfusion in the intensive care unit

Abstract: ÖZET:Diferansiye tiroit kanserlerinde TNM evreleme sisteminin 8. sürümünde neler değişti? Klinik pratiği nasıl etkileyecek?TNM evreleme sisteminin son olarak sekizinci sürümü (edisyonu) yayınlandı. Tiroit kanserleri TNM evreleme sisteminin 1987 yılında yayınlanan 4. sürümünde yer aldı. Literatürdeki kanıtlara dayalı olarak güncellenen TNM sisteminin her sürümü diğer kanserler gibi diferansiye tiroit kanserleri (DTC) için de bir önceki sürümüne göre önemli bazı farklılıklar içerir. Tiroit kanserleri için günümü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…Another study concluded that a lower minimum threshold value could be tolerated when making a decision on RBC transfusion (14). Furthermore, it has been reported that the use of a restrictive transfusion protocol may be a better strategy for prolonging survival (15). The average Hb of patients at transfusion in our study was 6.9 g/dl.…”
Section: Discussionmentioning
confidence: 54%
“…Another study concluded that a lower minimum threshold value could be tolerated when making a decision on RBC transfusion (14). Furthermore, it has been reported that the use of a restrictive transfusion protocol may be a better strategy for prolonging survival (15). The average Hb of patients at transfusion in our study was 6.9 g/dl.…”
Section: Discussionmentioning
confidence: 54%